2015
DOI: 10.1007/s00702-015-1468-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between ACE polymorphism, cognitive phenotype and APOE E4 allele in a Tunisian population with Alzheimer disease

Abstract: Angiotensin-converting enzyme (ACE) has shown altered activity in patients with neurological diseases. An insertion/deletion (I/D) polymorphism of the ACE gene encoding angiotensin-converting enzyme has been reported to be associated with the risk for Alzheimer's disease (AD), and is generally considered to be a disorder primarily affecting memory. We conducted a case-control study in a sample composed of 85 sporadic AD patients and 90 age- and sex-matched controls to investigate the possible effect of the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…The APOE gene polymorphism is associated with the risk of developing many central nervous system disorders. APOE polymorphism has been recognized as a genetic risk factor for the development of Alzheimer's disease in different populations ( Achouri-Rassas et al, 2015 , Kumar et al, 2015 , Zheng et al, 2016 ). In Chinese population, APOE polymorphism is associated with the risk of developing deep venous thrombosis ( Zhu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The APOE gene polymorphism is associated with the risk of developing many central nervous system disorders. APOE polymorphism has been recognized as a genetic risk factor for the development of Alzheimer's disease in different populations ( Achouri-Rassas et al, 2015 , Kumar et al, 2015 , Zheng et al, 2016 ). In Chinese population, APOE polymorphism is associated with the risk of developing deep venous thrombosis ( Zhu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…By different combinations of these three haplotypes, six genotypes (ɛ2/ɛ2, ɛ3/ɛ3, ɛ2/ɛ3, ɛ3/ɛ4, ɛ2/ɛ4, and ɛ4/ɛ4) are formed . Although the frequency of these alleles/genotypes varies among different populations, APOE ɛ3/ɛ3 is the most common genotype, and ε3 is the most predominant allele in most population . Several studies demonstrated that the APOE polymorphisms have been linked to the cardiovascular disease, lipoprotein glomerulopathy, and Alzheimer's disease II .…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Although the frequency of these alleles/genotypes varies among different populations, APOE ɛ3/ɛ3 is the most common genotype, and ε3 is the most predominant allele in most population. [18][19][20][21] Several studies demonstrated that the APOE polymorphisms have been linked to the cardiovascular disease, lipoprotein glomerulopathy, and Alzheimer's disease II. 22,23 APOE gene polymorphism is related to the effect of statins on lipid-lowering.…”
mentioning
confidence: 99%
“…The differences may be attributed to the small sample size and the possibility of different races, which were also reported in another study (Mathew et al, 2001). The formation of MCI may be influenced by several genes, and the ACE gene contributes only a slight effect (Vardy et al, 2012; Achouri-Rassas et al, 2016). ACE I/D polymorphism can be in a linkage disequilibrium with the true variants (McCrimmon et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…ACE I/D polymorphism can be in a linkage disequilibrium with the true variants (McCrimmon et al, 2012). Gene–environment interactions may also lead to discrepancies (Achouri-Rassas et al, 2016). …”
Section: Discussionmentioning
confidence: 99%